Impact of recycled polypropylene fibers on the density and strength of unreinforced concrete / Hasan Ali Abbas ... [et al.] - Ali Abbas, Hasan; Abbas Hashem, Mortada; Hussein, Muhammad Adam; Ahmed Nawaf, Miqdad (Smart Manufacturing Research Institute (SMRI), 2024)
Polypropylene (PP) is widely used in the construction industry to produce a variety of materials. Accordingly, a huge amount of waste is produced during or after the construction activity. The PP fiber provides a good alternative solution to enhance concrete properties and more sustainable concrete produced in terms of isolation and weight reduction. In this study, 24 concrete cubic samples are cast by adding different PP fiber content to characterize this fiber effect on concrete density and unconfined compressive strength (UCS). The results demonstrate that using higher fiber content of 2%, 6%, and 10% leads to a mass reduction that equals to 59, 157, and 290 kg compared to normal concrete per one cubic meter. However, at higher PP fiber content, the unconfined compressive strength decreases compared to the controlled samples. The concrete mix with 2% PP fiber revealed a higher value of compressive strength with increment by (10-12)% at age (7-28) days compared to normal concrete. The outcomes imply that using PP fiber contributes to the protection of the environment by reducing the quantity of PP waste from construction materials.